Perwujudan Kasih Setia Allah Terhadap Kesetiaan Rut - Shintia Maria Kapojos; Hengki Wijaya (Sekolah Tinggi Teologi Simpson, 2018)
Shintia Maria Kapojos, Hengki Wijaya, This paper aims to explain the manifestation of God's loyal love for Ruth who is faithful to her father-in-law, Naomi. The method used is the interpretation of the Old Testament narrative. Through this paper, the author will focus on Ruth's loyalty to Naomi as a manifestation of God's allegiance to man. This Old Testament narrative addresses explicitly the theme of Ruth's loyal love for Naomi and its theological and practical implications for believers to manifest God's loving kindness to others. Shintia Maria Kapojos, Hengki Wijaya, Tulisan ini bertujuan untuk menjelaskan perwujudan kasih setia Allah kepada Rut yang setia kepada mertuanya, Naomi. Metode yang digunakan adalah penafsiran narasi Perjanjian Lama. Melalui tulisan ini, penulis akan fokus kepada kesetiaan Ruth kepada Naomi sebagai manifestasi kesetiaan Allah kepada manusia. Narasi Perjanjian Lama ini secara khusus membahas tema kasih setia Ruth kepada Naomi dan implikasi teologis dan praktisnya bagi orang percaya untuk memanifestasikan kasih setia Tuhan kepada orang lain.